Scholarship and policy on urban densification: perspectives from city experiences. Issue 2 (1st April 2021) - Harrison, Philip; Klein, Garth; Todes, Alison
Abstract : Urban compaction and densification policy is widely advocated internationally, including for countries in the global South. Such advocacy draws on 'best practice' case examples, but these are frequently presented in decontextualised ways. Drawing from an account of densification processes and policies in six cities – Moscow, Curitiba, Sydney, Johannesburg, Delhi and São Paulo – the paper shows that while policy is sometimes similar, outcomes are deeply embedded in national and local contexts and are therefore variable and complex. In the polarised debate between compaction and managed sprawl, the fact is often missed that both sprawl and densification are happening simultaneously in most cities. Analysis of the cases also suggests that insufficient attention has been paid within both the analytical and policy literature to the influence of property markets and associated politics, the role of informality, and how politics and institutions shape the outcomes of compaction policy, including the agency of local people.